Determination of polluting emissions to control and reduce environmental pollution generated by vehicles - Cuba Cornejo, Carmen (2021)
The objective of this study is to determine the polluting emissions in the supervision for the reduction of environmental pollution caused by vehicle traffic in the Ica fencing,enclosure, being the type research, descriptive-explanatory level, non-experimental design, the population for For the purposes of the study, it was made up of all the arteries of Cercado de Ica and the sample considered were the streets with the highest vehicular traffic at rush hour, such as: Corner of Lima Street with La Libertad Street; Corner of Avenida San Martín and Avenida Municipality; Corner of Grau Avenue and Castrovirreyna Street; Corner of Avenida Grau and Calle la Mar. The questionnaire was used. Cars and motorcycles are responsible for the large CO emissions, in 46.72% and 37% of the total CO emissions emitted in the Ica fencing. It is concluded that we must institute measures and tasks that allow us to have an air quality surveillance program, which provides information in real time, which helps us make decisions quickly, in cases of increase in accumulation values. of atmospheric pollutants.